2017
DOI: 10.5935/0946-5448.20170013
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Patients Suffering from Anxiety and Depression: A Review

Abstract: Objectives: To review literature on the link between depression and anxiety in patients suffering from tinnitus. Method: A systematic review of published English-language literature was performed using PubMed, Ovid, and Cochrane databases. Results: Of the 56 eligible abstracts 15 were chosen to be included in the review. All articles showed an association of depression and anxiety in tinnitus patients. Conclusions: Because of the strong association between tinnitus, depression, and anxiety-all tinnitus patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 39 publications
(44 reference statements)
1
57
0
6
Order By: Relevance
“…Globus pharyngeus was found to be a significant predictor of severe anxiety (OR = 5.993) with a suggested moderate to high clinical significance. Several reports in the literature support the strong association of these symptoms with mental disorders , , . Some authors suggest a bidirectional relationship between tinnitus and dizziness and mental disorders .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Globus pharyngeus was found to be a significant predictor of severe anxiety (OR = 5.993) with a suggested moderate to high clinical significance. Several reports in the literature support the strong association of these symptoms with mental disorders , , . Some authors suggest a bidirectional relationship between tinnitus and dizziness and mental disorders .…”
Section: Discussionmentioning
confidence: 93%
“…clinical significance. Several reports in the literature support the strong association of these symptoms with mental disorders 9,68,[18][19][20]23. Some authors suggest a bidirectional relationship between tinnitus and dizziness and mental disorders.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recent systematic reviews [12][13][14] have addressed the theme in a broad way, presenting this probable association in general, but they do not identify the results by age group. As previously shown, the highest prevalence of tinnitus is centered in the elderly population, and thus, considering the changes resulting from the aging process, a careful investigation directed to this population is made necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of 56 abstracts conducted by Ziai et al concluded that there is mounting evidence supporting the association of tinnitus with depression and anxiety. 26 In the present study we have also tried to correlate the severity of tinnitus with severity of anxiety and depression; however, irrespective of the severity of tinnitus, most patients had only mild anxiety and depression. Thus, tinnitus should be understood as a neuropsychiatric or somatoform disorder syndrome.…”
Section: Discussionmentioning
confidence: 91%